Efeito da terapia periodontal não cirúrgica sobre a expressão de beta defensina-1 e índices glicêmicos em indivíduos com periodontite crônica saudáveis e portadores de Diabetes Mellitus tipo 2 - Lidiane Cristina Machado Costa (2016)
The human beta defensins (hBDs) may have a key role in susceptibility to diseases in the oral cavity. In addition to direct antimicrobial effect, the hBDs increase adaptive immunity. High glucose conditions in vitro, shown to be capable of inhibiting the expression of hBDs and contribute to the occurrence of infectious diseases associated with diabetic wounds. This study aimed to evaluate the beta defensins 1 (hBD-1)expression in gingival crevicular fluid (GCF) in healthy subjects (H), individuals with chronic periodontitis (P), and individuals with chronic periodontitis and diabetes mellitus compensated (PDMc) and decompensated (PDMd). Furthermore, the influence of nonsurgicalperiodontal therapy (NSPT) in this expression and glycemic control. Thus, this thesis is divided into 5 studies, as follows: 1) cross-sectional study to assess hBD-1 expression in FCG of H and P; 2) intervention study to evaluate the effect of NSPT on the hBD-1 expression in GCF of H and P; 3) cross-sectional study to assess hBD-1 expression in FCG of H, P, PDMc and PDMd; 4) intervention study to evaluate the effect of NSPT on the hBD-1 expression in FCG of PDMc and PDMd; 5) controlled clinical trial to evaluate the effect of NSPT on the glycemic indexes of PDMc and PDMd. The overall sample consisted of 80 individuals, been: 20 H, 20 P, 20 MCDP, and 20 PDMd. GCF samples were collected from healthy sites (h) sites with gingivitis (g) and periodontitis (p) of the same individual, totaling 800 samples of GCF, at baseline (T0) and after 2 monthsof NSPT (T1). Fasting glucose and glycated hemoglobin (HbA1c) were recorded at T0 and T1. The quantitation of hBD-1 was carried out by sandwich ELISA. In study 1, hBD- 1 levels in Hh were higher than in Ph. In P, there was no significant difference in thelevels of hBD-1 among all sites. In study 2, the NSPT increased hBD-1 levels in all sites of P. In study 3, significant intra-group differences were observed. Significant differences were found between Hh vs. Ph, Ph vs. PDMc(h), Hh vs. PDMd(g), Pg vs. PDMc(g), Hh vs. Pp, Hh vs. PDMd(p) e Pp vs. PDMc(p). In the study 4, PDMc(p) was significantly higher in T1 relative to T0. In individuals PDMd group, no significant differences were found at all sites between T1 and T0. In the study 5, there was significant improvement in periodontal parameters from T0 to T1 in both PDMc and PDMd groups. There was a significant reduction in HbA1c from T0 to T1 in PDMd group. Thus, the results indicate that the hBD-1 expression in individuals with periodontitis appears to be lower compared to healthy individuals, suggesting a potential protective role in hBD-1 susceptibility to chronic periodontitis. The NSPT was able to increase the hBD-1 levels in individuals with periodontitis in all sites, and to promote a reduction in HbA1c in decompensated diabetics.